Factors Influencing French Tourists to Visit Bali - Endi, Ferhadius; Prasetyo, Danang (Institut Pariwisata Trisakti, 2020)
This study discusses the factors that influence French tourists to visit Bali. This research is a qualitative descriptive study. The research data was obtained by observing, documenting and interviewing 48 French tourists who used the services of a travel agent during their vacation in Bali in 2019. To test the validity of the data, researchers used triangulation of techniques and sources. Then data analysis through the stages of data collection, data reduction, data display and drawing conclusions. Based on the results of research that has been conducted, it is found that there are 10 (ten) factors that influence French tourists to visit Bali; those are: (1) the beauty of the nature, (2) the hospitality of the Balinese people, (3) the rich history, local culture and traditions, (4) the competitive prices, (5) beaches and activities, (6) the traditional cuisine of Bali, (7) the convenience during vacation, (8) meditation and yoga facilities, (9) the availability of Francophone guide, and (10) the existence of Francophone community. The results of this study are expected to provide a strategic plan map for the development of tourism especially in Bali and in Indonesia in general.